Performance and Poverty Convergence in North Sumatra - Arif Rahman; Sukma Hayati Hakim; Muhammad Syafii (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
North Sumatra is one of the growth centers in Indonesia. However, its number of poverty is one of the highest nationally. This study aimed to see the performance and prove whether there is a convergence of poverty in North Sumatra Province during the years 2011-2021. The analytical method used included quantitative descriptive analysis. Through the Klassen quadrant which was divided into two periods, it can be seen that some regions have moved quadrants and some other regions have moved towards quadrant lines at different levels. The situation showed serious inequality in some areas that were in quadrant 4. The results of the Williamson index showed that the degree of inequality in poverty levels between regions tended to decrease, although there has been an increase in several years of observation. Through the sigma convergence test, it was strongly indicated that there was a dispersion of poverty levels between regions towards one common ground. It has been further confirmed by the absolute beta convergence test. Real income per capita and RLS that included in the conditional convergence model have proven to accelerate the process of poverty convergence between regions in North Sumatra.